Patentes biotecnológicas y genéticas: enfoque jurídico y ético - Bergel, Salvador (2012)
Biotechnological and genetic patents: legal and ethical approach Biotechnology’s entry to patentable inventions field and ethical questions generated are studied from the analysis between moral and legal order relationship. There are several cases where standards concerning patents came into conflict with public order idea or moral concerns, such as human cloning processes or genetic identity modification of human beings or animals. Among these problems, patenting of human genetic material is pointed out. Different views on the issue are carefully analyzed; this piece of writing a does not pretend to close the debate but to expose the key points involved.